Energy, Exergic and Economic Analyses of a Novel Hybrid Solar–Gas System for Producing Electrical Power and Cooling - Qun Ge; Xiaoman Cao; Fumin Guo; Jianpeng Li; Cheng Wang; Gang Wang (Energies)
This paper aims to evaluate the feasibility and performances of a novel hybrid solar–gas system, which provides electric power and cooling. By using Ebsilon (V15.0) software, the operation, advanced exergic and economic analyses of this hybrid system are conducted. The analysis results show that the total electric power and energy efficiency of the hybrid system are 96.0 MW and 45.8%. The solar energy system contributes an electric power of 9.0 MW. The maximum cooling load is 69.66 MW. The exergic loss and exergic efficiency of the whole hybrid system are 119.1 MW and 44.6%. The combustion chamber (CC) has the maximum exergic loss (56.5 MW). The exergic loss and exergic efficiency of the solar direct steam generator (SDSG) are 28.5 MW and 36.2%. For the air compressor (AC), CC, heat recovery steam generator (HRSG) and refrigeration system (CSS), a considerable part of the exergic loss is exogenous. The avoidable exergic loss of the CC is 11.69 MW. For the SDSG, there is almost no avoidable exergic loss. Economic analysis shows that for the hybrid system, the levelized cost of energy is 0.08125 USD/kWh, and the dynamic recycling cycle is 5.8 years, revealing certain economic feasibility. The results of this paper will contribute to the future research and development of solar–gas hybrid utilization technology to a certain extent.